ROBUST TUNING OF POWER SYSTEM STABILIZER PARAMETERS USING THE MODIFIED HARMONIC SEARCH ALGORITHM - Abdul Kareem, Hiba Zuhair; Hasan Mohammed , Husam; Aqeel Mohammed , Ameer (IIUM Engineering Journal, 2020)
Power System Stabilizer is used to improve power system low frequency oscillations during small disturbances. In large scale power systems involving a large number of generators, PSSs parameter tuning is very difficult because of the oscillatory modes’ low damping ratios. So, the PSS tuning procedure is a complicated process to respond to operation condition changes in the power system. Some studies have been implemented on PSS tuning procedures, but the Harmony Search algorithm is a new approach in the PSS tuning procedure. In power system dynamic studies at the first step system total statues is considered and then the existed conditions are extended to the all generators and equipment. Generators’ PSS parameter tuning is usually implemented based on a dominant operation point in which the damping ratio of the oscillation modes is maximized. In fact the PSSs are installed in the system to improve the small signal stability in the system. So, a detailed model of the system and its contents are required to understand the dynamic behaviours of the system. In this study, the first step was to linearize differential equations of the system around the operation point. Then, an approach based on the modified Harmony Search algorithm was proposed to tune the PSS parameters. ABSTRAK: Penstabil Sistem Kuasa digunakan bagi meningkatkan sistem kuasa ayunan frekuensi rendah semasa gangguan kecil. Dalam sistem kuasa berskala besar yang melibatkan sebilangan besar penjana, penalaan parameter PSS adalah sangat sukar kerana nisbah corak ayunan redaman yang rendah. Maka, langkah penalaan PSS adalah satu aliran rumit bagi mengubah keadaan operasi sistem kuasa. Beberapa kajian telah dilaksanakan pada prosedur penalaan PSS, tetapi algoritma Harmony Search merupakan pendekatan baru dalam prosedur penalaan PSS. Dalam kajian sistem kuasa dinamik ini, langkah pertama adalah dengan memastikan status total sistem dan keadaan sedia ada diperluaskan kepada semua penjana dan peralatan. Parameter penalaan generator PSS biasa dilaksanakan berdasarkan titik operasi yang dominan di mana nisbah corak ayunan redaman dimaksimumkan. Malah PSS dipasang di dalam sistem bagi meningkatkan kestabilan isyarat kecil dalam sistem. Oleh itu, model terperinci sistem dan kandungannya diperlukan bagi mengenal pasti perihal sistem dinamik. Kajian ini, dimulai dengan melinear sistem persamaan pembezaan pada titik operasi. Kemudian, pendekatan berdasarkan algoritma Harmony Search yang diubah suai telah dicadangkan bagi penalaan parameter PSS.